2018
DOI: 10.1007/s12182-018-0278-2
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic performance of Cu- and Zr-modified beta zeolite catalysts in the methylation of 2-methylnaphthalene

Abstract: 2,6-Dimethylnaphthalene (2,6-DMN) is a commercially important chemical for the production of polyethylenenaphthalate and polybutylene naphthalate. However, its complex synthesis procedure and high production cost significantly reduce the use of 2,6-DMN. In this study, the synthesis of 2,6-DMN was investigated with methylation of 2-methylnaphthalene (2-MN) over metal-loaded beta zeolite catalysts including beta zeolite, Cu-impregnated beta zeolite and Zr-impregnated beta zeolite. The experiments were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…They are considered a viable alternative to chemical catalysts because they are renewable, non‐toxic, biodegradable, easy and safe to develop, non‐corrosive, and generate no spent water. The study of the effects of Cu‐ and Zr‐impregnated beta zeolite catalysts on 2 MN methylation by Gulec et al 37 . concluded that unconventional cheap naphthalene source from coal tar naphthalene oil fraction, a waste product, should be employed to reduce the cost of 2,6‐DMN production.…”
Section: Introductionmentioning
confidence: 99%
“…They are considered a viable alternative to chemical catalysts because they are renewable, non‐toxic, biodegradable, easy and safe to develop, non‐corrosive, and generate no spent water. The study of the effects of Cu‐ and Zr‐impregnated beta zeolite catalysts on 2 MN methylation by Gulec et al 37 . concluded that unconventional cheap naphthalene source from coal tar naphthalene oil fraction, a waste product, should be employed to reduce the cost of 2,6‐DMN production.…”
Section: Introductionmentioning
confidence: 99%
“…The development of polymer nanocomposites has produced a new class of materials with superior mechanical, thermal, and transport properties . These properties depend on several factors, such as the polymer synthesis method, the mixing process, and the nanoreinforcement . In this regard, Cordero et al .…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The development of polymer nanocomposites has produced a new class of materials with superior mechanical, 13 thermal, 14 and transport properties. 15 These properties depend on several factors, such as the polymer synthesis method, 16,17 the mixing process, 18 and the nanoreinforcement. 13 In this regard, Cordero et al 19 found that the incorporation of a small amount of nanocellulose obtained by hydrolysis can have a substantial improvement of the mechanical properties of polyurethane foams (PUFs) synthesized from castor oil.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, besides the β‐NA, it is necessary to add one of crystallization synergists such as nano‐CaCO 3 and molecular sieve to enhance the percentage of β‐crystals and the toughening and strengthening performance, which are favorable for the foaming process. Molecular sieve is a hydrated aluminosilicate with screening molecular action, which has a regular pore structure as well as catalytic and adsorption effects …”
Section: Introductionmentioning
confidence: 99%